MAIN PRIORITIES AND DIRECTIONS OF SCIENTIFIC AND TECHNOLOGICAL DEVELOPMENT OF COUNTRIES IN THE 21ST CENTURY - Abdullayeva Guliraino (Uzbekistan Open Conference, 2025)
The article examines the main priorities and directions of scientific and technological development of countries in the 21st century. It analyzes key global trends in technological progress, including digitalization, the development of artificial intelligence, green energy, biotechnology, space exploration, and the creation of new materials. Special attention is given to sustainable development, international cooperation, and the social aspects of scientific innovation. It is noted that the formation of a knowledge-based economy and the enhancement of technological independence have become strategic goals for most countries.
Keywords: scientific and technological development; innovation; digitalization; artificial intelligence; biotechnology; energy; sustainable development; new materials; space technology; knowledge economy